Distinct signals generate repeating striped pattern in the embryonic parasegment. - Hatini, V.; DiNardo, S. (Molecular Cell, 2001)
How repeating striped patterns arise across cellular fields is unclear. To address this we examined the repeating pattern of Stripe (Sr) expression across the parasegment (PS) in Drosophila. This pattern is generated in two steps. First, the ligands Hedgehog (Hh) and Wingless (Wg) subdivide the PS into smaller territories. Second, the ligands Hh, Spitz (Spi), and Wg each emanate from a specific territory and induce Sr expression in an adjacent territory. We also show that the width of Sr expression is determined by signaling strength. Finally, an enhancer trap in the sr gene detects the response to Spi and Wg, but not to Hh, implying the existence of separable control elements in the sr gene. Thus, a distinct inductive event is used to initiate each element of the repeating striped pattern.